Hubungan Antara Masa Kerja dan Kelelahan Dengan Stres Kerja Pada Pekerja Konstruksi - Habiba Kamila Fatin; Rini Handayani; Ahmad Irfandi; Putri Handayani (Jurnal Ilmu Kesehatan dan Gizi, 2023)
The results of a preliminary study conducted by researchers using the DASS 21 questionnaire and stress impact questionnaire on 10 workers at PT Nindya Citra Kharisma KSO's Manggarai "Mainline 1" project in 2023, found that there were workers who experienced stress with the most impact felt feeling easily tired. The purpose of this study is to determine the relationship between working time and fatigue with work stress. This study used a cross sectional design with a population of 60 people and the sampling method used was a total sampling of 50 people. Data analysis using univariate and bivariate analysis with chi square test. The results of the analysis showed that as many as 29 (58%) workers experienced stress. There is no relationship between years of service (p value = 1,000; PR = 0.967) with work stress and there is a relationship between fatigue and work stress (p value = 0.45; PR 2,057). It can be concluded that fatigue is related to work stress while working period are not related to work stress. Researchers suggest that a work fatigue and stress control program be held through a shift work system so that the duration of work does not exceed NAB (8 hours / day).